Antimyeloma Effects of the Heat Shock Protein 70 Molecular Chaperone Inhibitor MAL3-101. (29th September 2011) - Braunstein, Marc J.; Scott, Sadeaqua S.; Scott, Craig M.; Behrman, Shannon; Walter, Peter; Wipf, Peter; Coplan, Jeremy D.; Chrico, William; Joseph, Danielle; Brodsky, Jeffrey L.; Batuman, Olcay
Abstract : Multiple myeloma (MM) is the second most common hematologic malignancy and remains incurable, primarily due to the treatment-refractory/resistant nature of the disease. A rational approach to this compelling challenge is to develop new drugs that act synergistically with existing effective agents. This approach will reduce drug concentrations, avoid treatment resistance, and also improve treatment effectiveness by targeting new and nonredundant pathways in MM. Toward this goal, we examined the antimyeloma effects of MAL3-101, a member of a new class of non-ATP-site inhibitors of the heat shock protein (Hsp) 70 molecular chaperone. We discovered that MAL3-101 exhibited antimyeloma effects on MM cell lines in vitro and in vivo in a xenograft plasmacytoma model, as well as on primary tumor cells and bone marrow endothelial cells from myeloma patients. In combination with a proteasome inhibitor, MAL3-101 significantly potentiated the in vitro and in vivo antimyeloma effects. These data support a preclinical rationale for small molecule inhibition of Hsp70 function, either alone or in combination with other agents, as an effective therapeutic strategy for MM.